2007
DOI: 10.1007/s00423-006-0132-7
|View full text |Cite
|
Sign up to set email alerts
|

The axillary access in unilateral thyroid resection

Abstract: This study shows that endoscopic thyroid surgery approximates the norms of endocrine neck surgery. The presented method is useful in thyroid surgery for patients with single nodules and a small thyroid gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
0
22
0
2
Order By: Relevance
“…The majority of the authors reporting on endoscopic thyroidectomy call for an intraoperative identification of this nerve [1,3,8,16,17,19,23] due to the fact that postoperative RLN palsy is one of the largest problems in thyroid surgery. Dralle et al [1] reported that it is followed by an enormous economic and health care burden, an increasing number of medicolegal proceedings and a significant disruption of socioeconomic outcome for the afflicted patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the authors reporting on endoscopic thyroidectomy call for an intraoperative identification of this nerve [1,3,8,16,17,19,23] due to the fact that postoperative RLN palsy is one of the largest problems in thyroid surgery. Dralle et al [1] reported that it is followed by an enormous economic and health care burden, an increasing number of medicolegal proceedings and a significant disruption of socioeconomic outcome for the afflicted patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, quite a number of similar reports have been published, all of them describing an access outside the front neck region. Such accesses are the lateral neck [11] , chest [12,13] , axillary [14][15][16] , a combined axillary bilateral breast [17][18][19] or a bilateral axillary breast approach [20] . It is the aim of such procedures to achieve an optimal cosmetic result while keeping the access trauma acceptable [21,22] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hierzu gehören beispielsweise der dorsale Zugang am Hals, der thorakale, axilläre oder der kombinierte bilaterale inframammäre und axilläre Zugang. Hierdurch soll ein optimales kosmetisches Ergebnis erreicht und das Zugangstrauma so gering wie möglich gehalten werden [9,10,11,12,13,14,15]. Allerdings stehen einige der sogenannten minimal-invasiven Verfahren wie beispielsweise der axilläre oder inframammäre Zugang zur Schilddrüsenloge aufgrund des ausgeprägten Gewebetraumas im Bereich des Zugangsweges und der lagen Operationszeiten in der Kritik [16,17].…”
Section: Diskussionunclassified